Religiosity and Spirituality in the Modernization Framework According to Sutan Takdir Alisjahbana - Toresano, Waode Zainab Zilullah; Rahayu, Endang Sri (Proceedings of International Conference on Muslim Society and Thought, 2024)
The background of this research is the phenomenon of a crisis of human values within the framework of modernization in contemporary discourse, which necessitates ‘change’. In Sutan Takdir Alisjahbana’s perspective, modernity, on the one hand, has a positive impact because it encourages the realization of progress based on knowledge. On the other hand, according to Sutan Takdir Alisjahbana, modernity can cause problems, such as paradoxes and tragedies. Therefore, modernization impacts religiosity and spirituality, which are inherent in humans. This research aims to analyze religiosity and spirituality within the framework of modernization referring to Sutan Takdir Alisjahbana’s point of view. Sutan Takdir Alisjahbana is not only known as an Indonesian litterateur and cultural figure but also as a philosopher familiar with the discourse of philosophy. This research employs a methodology using library research techniques, including collecting, reading, studying, reviewing, dissecting, and researching books and journal articles related to this topic. In conducting this research, researchers utilized a philosophical approach. The result of this research is that Sutan Takdir Alisjahbana’s philosophical thought views ‘modernity’ within the framework of modernization, can place religiosity and spirituality in a wise response as a human expression in the search for and journey towards the Holy One/ the Ultimate Reality.